House Dust Mite and Cat Dander Extract Induce Asthma-Like Histopathology with an Increase of Mucosal Mast Cells in a Guinea Pig Model - Patricia Ramos-Ramírez; Jielu Liu; Sofia Mogren; Joshua Gregory; Malin Noreby; Anne Petrén; Ying Lei; Henric Olsson; Marianne van Hage; Jukka Kervinen; Lars Hellman; Cecilia Andersson; et al. (Journal of Immunology Research)
Background. Asthma is a chronic inflammatory disease with structural changes in the lungs defined as airway remodelling. Mast cell responses are important in asthma as they, upon activation, release mediators inducing bronchoconstriction, inflammatory cell recruitment, and often remodelling of the airways. As guinea pigs exhibit anatomical, physiological, and pharmacological features resembling human airways, including mast cell distribution and mediator release, we evaluated the effect of extracts from two common allergens, house dust mite (HDM) and cat dander (CDE), on histopathological changes and the composition of tryptase- and chymase-positive mast cells in the guinea pig lungs. Methods. Guinea pigs were exposed intranasally to HDM or CDE for 4, 8, and 12 weeks, and airway histology was examined at each time point. Hematoxylin and eosin, Picro-Sirius Red, and Periodic Acid-Schiff staining were performed to evaluate airway inflammation, collagen deposition, and mucus-producing cells. In addition, Astra blue and immunostaining against tryptase and chymase were used to visualize mast cells. Results. Repetitive administration of HDM or CDE led to the accumulation of inflammatory cells into the proximal and distal airways as well as increased airway smooth muscle mass. HDM exposure caused subepithelial collagen deposition and mucus cell hyperplasia at all three time points, whereas CDE exposure only caused these effects at 8 and 12 weeks. Both HDM and CDE induced a substantial increase in mast cells after 8 and 12 weeks of challenges. This increase was primarily due to mast cells expressing tryptase, but not chymase, thus indicating mucosal mast cells. Conclusions. We here show that exposure to HDM and CDE elicits asthma-like histopathology in guinea pigs with infiltration of inflammatory cells, airway remodelling, and accumulation of primarily mucosal mast cells. The results together encourage the use of HDM and CDE allergens for the stimulation of a clinically relevant asthma model in guinea pigs.